外科手术及利妥昔单抗对原发胃弥漫大B细胞淋巴瘤患者生存的影响 (Zhonghua Xue Ye Xue Za Zhi, 2016)
OBJECTIVE: To evaluate the outcome of surgical resection and rituximab for treatment of primary gastric diffuse large B cell lymphoma (PGDLBCL). METHODS: Data of 83 patients with primary gastric diffuse large B cell lymphoma were reviewed retrospectively. 40 patients received surgical resection followed by chemotherapy, and the other 43 patients chemotherapy alone. The two groups were further divided into four sub-groups according to chemotherapy regimens (CHOP or R-CHOP). Overall survival (OS) and progression free survival (PFS) as two prognostic indexes were analyzed. RESULTS: The median age of these 83 cases at diagnosis was 52 years (range, 20–76 years) with a male-to-female ratio of 43 to 40. And the follow-up duration ranged from 4–59 months (mean 36 months). The 5-year PFS for the patients received surgery and chemotherapy was 66.7%. PFS for the patients received chemotherapy alone was 82.6%. And 5-year OS for these two groups was 68.4% and 85.9%,respectively. OS and PFS of chemotherapy alone group were better than the other one without statistically significance. In the combined group, the 5-year OS were 73.6% for patients received R-CHOP and 64.2% for patients received CHOP; the 5-year-PFS were 71.2% and 62.5%, respectively. Meanwhile, the 5-year OS for patients received R-CHOP and CHOP were 85.7% and 83.5%; the 5-year-PFS were 83.4% and 81.8%, respectively. The OS and PFS did not differ significantly (P>0.05) between two chemotherapy regimens. According to the Lugano stage, those who received chemotherapy alone for the patients with advanced stage (Ⅱ2, ⅡE or Ⅳ) had better OS compared with received surgery and chemotherapy. A significant difference was found between the two groups (P<0.05). However for the patients with early stage (Ⅰ or Ⅱ2), there was no statistically significance between the two groups (P>0.05). Univariate analysis showed that age, ECOG, Lugano stage, level of LDH and IPI score (P<0.05) were factors of survival in patients with PGDLBCL. And multivariate analysis showed that IPI score was an independent prognostic factor for OS. CONCLUSION: The survival of the patients received combined surgery and chemotherapy was not superior to those received chemotherapy alone. There was no statistically significance between two different regimens for prognosis of PGDLBCL. Because of poor quality of life caused by surgery, surgery shouldn't now been recommended for the patients with PGDLBCL without operative indication. Rituximab had no positive influence on OS and PFS in most patients with PGDLBCL, but this result should be confirmed by further large sample and multi-center study.